Alternative agrifood movements patterns of convergence and divergence - Rivera-Ferre, Marta; Constance, Douglas; Renard, María Christine (Research in rural sociology and development ;, 2014)
This volume explores the issues of convergence and divergence in alternative agrifood movements through a theoretical and empirical engagement of the topic by notable agrifood researchers from Europe, North America and South America. It probes the degree to which the numerous alternative agrifood movements that have emerged in recent years in response to the legitimation crisis of conventional agriculture have converged around a central alternative thesis or pursued divergent paths of development. Some alternative agrifood movements represent radical critiques of conventional agriculture that challenge the existing system while other movements engage in reformist and accommodative approaches that are viewed as complimentary. The book begins with chapters that enhance the theoretical discussions on the pathways and obstacles to convergence followed by empirical case studies on organics, food sovereignty, landless workers, alternative food systems, and food policy councils.